2011
DOI: 10.1186/1758-5996-3-3
|View full text |Cite
|
Sign up to set email alerts
|

New clinical score to diagnose nonalcoholic steatohepatitis in obese patients

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is the most frequent disease associated with abnormal liver tests that is characterized by a wide spectrum of liver damage, ranging from simple macro vesicular steatosis to steatohepatitis (NASH), cirrhosis or liver carcinoma. Liver biopsy is the most precise test to differentiate NASH from other stages of NAFLD, but it is an invasive and expensive method. This study aimed to create a clinical laboratory score capable of identify individual with NASH in severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 19 publications
1
29
1
1
Order By: Relevance
“…These results suggest a reduction in liver fat content in our patients as well. Furthermore, longitudinal studies show a reduction in FLI and NASH-Scores at the end of the study period suggesting a decrease of NAFLD and NASH in various participants due to the achieved weight loss [23,24]. However, our results show that fetuin-A is not altered after 52 weeks although weight and single values as well as scores of NAFLD suggest that the disease has improved.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…These results suggest a reduction in liver fat content in our patients as well. Furthermore, longitudinal studies show a reduction in FLI and NASH-Scores at the end of the study period suggesting a decrease of NAFLD and NASH in various participants due to the achieved weight loss [23,24]. However, our results show that fetuin-A is not altered after 52 weeks although weight and single values as well as scores of NAFLD suggest that the disease has improved.…”
Section: Discussioncontrasting
confidence: 56%
“…Statistical analysis: Scoring systems used to detect NAFLD were the FLI = (e 0.953 × ln (triglycerides in mg/dl) + 0.139 × BMI in kg/m² + 0.718 × ln (GGT in U/l) + 0.053 waist circumference in cm -15.745) / (1 + e 0.953 × ln (triglycerides in mg/dl) + 0.139 × BMI in kg/m² + 0.718 × ln (GGT in U/l) + 0.053 × waist circumference in cm -15.745) × 100 [23] and the NASH-Score by gaining one point each for triglycerides ≥ 200 mg/dl, AST/ALT ≤ 1, ALT ≥ 30 IU/l and GGT ≥ 30 IU/ while NASH is probable at ≥ 3 points [24]. The Homeostasis model assessment insulin resistance index (HOMA-IR) was calculated by Insulin [µU/ml] X Glucose [mmol/l] / 22.5 [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we confirmed that ezetimibe improves insulin resistance by reducing fasting IRI and HOMA-IR. The serum ALT level and the AST/ALT ratio, which are usually low in patients with fatty liver 17) , were significantly decreased and increased, respectively after ezetimibe monotherapy in patients with high basal ALT levels. Although we did not confirm fatty liver using ultrasonography or computed tomography, these results suggest that ezetimibe improves fatty liver.…”
Section: Discussionmentioning
confidence: 93%
“…The basal AST/ALT ratio, which is usually low in patients with fatty liver 17) , was significantly lower in the high ALT group than in the normal ALT group. After 12 weeks of ezetimibe treatment, the AST/ALT ratio was significantly increased in the high ALT group, whereas, conversely, that in the normal ALT group significantly decreased (Table 3).…”
Section: Methodsmentioning
confidence: 95%